1989
DOI: 10.2514/3.10174
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Runge-Kutta method for unsteady rotor/stator interaction

Abstract: AbetractA quastthree-dimensional rotor/statcr analysis has been developed for blade-teblade flows in turbomachinery. The analysis solves the unsteady M e r OT thin-layer Navier-Stokes equations in a body-fitted coordinate system. It accounts for the effects of rotation, radiw change, and stream-surface thickness. The Baldwirr Lomax eddy-viscosity model is used for turbulent flows. The equations are integrated in time using a four-stage RungeKutta scheme with a constant time step. Results are shown for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Moreover, they can be used as target solutions for fine-tuning steady multi-row pitch-averaging techniques. The works of Erdos et al (1977), Rai (1987), Lewis et al (1987), Jorgenson and Chime (1988), Giles (1988a), and Rao et al (1992) are some examples of basic historical contributions to this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they can be used as target solutions for fine-tuning steady multi-row pitch-averaging techniques. The works of Erdos et al (1977), Rai (1987), Lewis et al (1987), Jorgenson and Chime (1988), Giles (1988a), and Rao et al (1992) are some examples of basic historical contributions to this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Significant experimental and numerical research has been performed over the last several years on highlighting and understanding the unsteady aerodynamics of multi-stage turbomachinery (e.g., Reinmoller et al, 2001;Arnone et al, 2001;Gombert and Hohn, 2001;Dorney et al, 2001;Clark et al, 2000;Busby et al, 1998;Rao et al, 1994;Chen et al, 1994;Sharma et al, 1992;Takahashi and Ni, 1991;Giles, 1990;Jorgenson and Chima, 1990;Rai, 1987;Dring et al, 1992). Much of this work has focused on quantifying the unsteady flow field resulting from the interaction between rotors and stators in terms of aerodynamic performance and airfoil surface unsteady pressure.…”
Section: Introductionmentioning
confidence: 99%
“…This approach, at first glance, appears not to be well suited for the prediction of unsteady flows due to the ad hoc nature of the implicit portion of the algorithm. Recently, however, Jorgensen and Chima [4] demonstrated that such algorithms may be tailored for the unsteady flow problem to yield acceptable results.…”
Section: Description Of the Problemmentioning
confidence: 99%
“…(Re=9500, t=1.0)xvii GCGTVD predicted streamline pattern for impulsively started cylinder flow. (Re=9500, t=1 4). 232 GCGTVD predicted streamline pattern for impulsively staxted cylinder flow.…”
mentioning
confidence: 95%
See 1 more Smart Citation